PERANAN SOCIAL CAPITAL DAN INFRATRUKTUR SERTA SEKTOR OFF FARM PADA PENDAPATAN MASYARAKAT AGROFORESTRI - Agus Kurniawan Damanik; Samsul Bakrie; Christine Wulandari (Journal of People, Forest and Environment, 2021)
For the sake of sustaining transformation to off farm at rural economic and well planned, the contribution of physical capital and social capital in promoting community income in agroforestry community needs to be revealed through a systematic research, especially for villages located around suburban areas such as Sidoharjo and Jati Agung Villages, South Lampung. This study aimed at determining the contribution of physical capital, social capital, infrastructure, and sources of income outside of agroforestry activities  (off farm). In order to test the role of social and physical capitals, physical infrastructure, and the off farm sector on house hold income we employed Spearmen Correlation at confident level of 5 and 10%. In pursuing these objective, a semi-structured survey was conducted to 90 households in the two villages.  This result connoted that the house hold income was affected by : [a] social capital, especially network element (P-value = 0.079), [b] physical capital (land ownership P-value = 0.004 and cattle P-value = 0.003), [c] Off farm sector especially for the home industry (P- value=0.000) and [d] infrastructure, especially the quality of rural roads (P-value=0.080).  It is recommend that conduct research on the development of community empowerment policies so that they voluntarily leave forest land occupations through the development of a cow agrosilvopasture partnership